The symphonies of Charles Villiers Stanford: constructing a national identity? - White, J; Jonathan Paul White (2014)
Writing in 2001, musicologist Axel Klein concluded that Stanford’s reception history has been significantly impacted by the complicated national identities surrounding both the composer and his music. A lifelong devotee of the nineteenth-century Austro-Germanic tradition, Stanford’s status as an Irish-born leading figure of the ‘English’ Musical Renaissance has compromised the place that the composer and his musical output occupy within the history of Western music. Stanford is well-known for being an outspoken critic on matters musical and Irish. Although his views seldom appear ambiguous, there is still a sense that the real Stanford remains partially obscured by his opinions. Through an examination of his symphonic works, this thesis seeks to readdress our understanding of Stanford and his relationship with Ireland and the musical community of his time. Although A. Peter Brown has stated that the symphony was not a central genre for the composer, it is my argument that, on the contrary, the symphony was a pivotal form for him. Considering these works within the broader history of the symphony in Europe in the nineteenth century, and through a critical examination of Stanford’s relationship with Ireland, this thesis seeks to demonstrate that these seven works can be read as an allegory for the composer’s relationship both with his homeland and with the musical community of his time. His struggle to combine the universality of symphonic expression with a need to articulate his Irish identity parallels Stanford’s own attempts to integrate himself within both British and European musical communities, and further demonstrates, in his eventual rejection of it, that it was only when he attempted to forge a more individualistic path through his music that he found a way of expressing his individual Irish identity.